O comportamento dos consumidores idosos no consumo de entretenimento antes e após a aposentadoria: uma abordagem do paradigma do life course - PINHEIRO, Taluhama Guimarães Rosário. (2017)
This work used as reference the Life Course Paradigm to study the patterns of behavior of the elderly consumer behavior after the retirement event. We sought to identify the elderly consumer behavior about the entertainment before retirement event and what possible changes perceived in entertainment consumption behavior after the retirement of the event to be instated in their life. The choice of the theme occurred over the lack of existing research focused on the behavior of older consumers, the entertainment industry, as well as the growing importance of this segment of the population that is growing in percentage terms in the whole of the population. The methodological option was given by qualitative research for exploratory and descriptive purposes, using as a research technique, the study of multiple cases. Twenty-two in-depth interviews were conducted using a semi-structured script in the city of Salvador, State of Bahia, whose content was studied through content analysis. After the transcription of the scripts, Coding frames were used to reduce, encode and categorize the data by themes: Represented Roles, Types of Entertainment and Emotions. The result of the data was segmented according to the times used in the survey, with Time 1 corresponding to the period of 5 years before retirement, Time 2 to the moment the retirement event was established, and Time 3 the current moment In which the interviewee is. The study was carried out using the study model of the Paradigm of the Life Course - PLC by normative perspective to analyze and interpret the results of the research by represented roles. The results found are in line with the theory proposed in the Moschis PLC model (2007), in which it was noticed that the elderly consumer presents behavioral changes in the consumption of entertainment after the retirement event, due to the new roles represented, as well as new responsibilities And functions. Finally, the paper pointed out the limitations found in the research and mentioned some suggestions for future studies.